2011
DOI: 10.1002/rra.1382
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and evaluation of large‐scale river restoration planning in Germany to better link river research and management

Abstract: In December 2008, the draft programmes of measures (PoM) have been published in the EU member states, which list the measures that will be taken to enhance the ecological status of surface and groundwater bodies, and to reach the environmental objectives of the EU-Water Framework Directive (WFD). We have analysed the German PoM to identify the main pressures and the restoration measures water managers planned to implement in streams and rivers. The objective was to evaluate the PoM and to identify the main, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Creating a new, more natural channel planform is increasingly used as a restoration measure to improve the hydromorphological state of rivers [e.g., Gurnell et al ., ; Pedersen et al ., ]. Moreover, enhancing natural channel dynamics and creating a more natural channel planform are among the most frequently designated hydromorphological measures in the river management [ Kail and Wolter , ]. The results of this study show that a newly created restored channel potentially increases in channel dynamics and hence, sediment output are high until the river banks and floodplain get vegetated with a more pronounced effect if seeds are dispersed by flow compared to a uniform distribution of seeds (which is comparable to planting on the floodplain).…”
Section: Discussionmentioning
confidence: 99%
“…Creating a new, more natural channel planform is increasingly used as a restoration measure to improve the hydromorphological state of rivers [e.g., Gurnell et al ., ; Pedersen et al ., ]. Moreover, enhancing natural channel dynamics and creating a more natural channel planform are among the most frequently designated hydromorphological measures in the river management [ Kail and Wolter , ]. The results of this study show that a newly created restored channel potentially increases in channel dynamics and hence, sediment output are high until the river banks and floodplain get vegetated with a more pronounced effect if seeds are dispersed by flow compared to a uniform distribution of seeds (which is comparable to planting on the floodplain).…”
Section: Discussionmentioning
confidence: 99%
“…Restored longitudinal connectivity might not result in quantifiable biotic improvement if the segments up-and downstream of a barrier already contain the species, if no new or essential habitats become available for the species, or if connectivity measures are not accompanied by habitat enhancements (Kail and Wolter 2011). The overall importance of accessible habitats was underlined by the results of the mixed models, indicating that habitat suitability and the dispersal from proximal source populations govern the spatial distribution of freshwater fishes.…”
Section: With Interactions No Interactions With Interactions No Intermentioning
confidence: 99%
“…This study showed that gravel bottom ramps can effectively fulfill multiple management goals in regulated rivers by maintaining river continuity and providing compensatory habitat (Kail & Wolter ). Although a more holistic restoration of the geomorphic processes and hydrology would be desirable to create and maintain gravel bars and riffles (Beechie et al ), the design of the bottom ramps also addressed flood control and water table management objectives.…”
Section: Discussionmentioning
confidence: 99%